Electron Acceleration by a Radially Polarized Laser Pulse in an Azimuthal Magnetic Field (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Laser acceleration by radially polarized laser beams takes advantage of the strong longitudinal electric field component at the beam centre. When the laser field intensity is sufficiently high, it can push electrons initially at rest at the beam waist outside the Rayleigh zone and accelerate them to relativistic velocities along the laser axis. To obtain the best results in terms of electron dynamics and energy estimation, we suggest that the electrons could be accelerated to a very high energy level by the radially polarized laser pulse. The additionally used azimuthal magnetic field helps to retain the electron energy during acceleration. In this paper, we describe the electron energy scales with laser power and we explain how the laser beam parameter and the magnetic field both can be optimized for maximal acceleration.
Keywords: Laser acceleration; Radially polarized laser beam